Effectiveness of multimodal active physiotherapy for chronic knee pain: a 12-month randomized controlled trial follow-up study - Cui, Xinwen; Zhao, Peng; Guo, Xuanhui; Wang, Jialin; Han, Tianran; Zhang, Xiaoya; Zhou, Xiao; Yan, Qi (Frontiers in Physiology, 2024)
Active physiotherapy (APT) embraces a patient-centered approach, prioritizing self-management within the biopsychosocial model and involving active patient movements. Beyond structured exercise, APT incorporates pain neuroscience education, Mulligan Mobilization (MWM), and active myofascial release techniques to integrate sensory-motor information for functional recovery and pain relief. This study aims to rigorously compare the effectiveness of APT versus conventional physical therapy (CPT) on pain and functional outcomes in patients with chronic knee pain. Eighty-seven patients with symptomatic and radiographically confirmed knee pain were included in this 12-month follow-up of a randomized controlled trial, conducted at a national institute and a rehabilitation clinic. Patients were randomized to either APT (n = 44) or CPT (n = 43). The APT protocol integrated pain neuroscience education, MWM, active myofascial release techniques, and structured exercises focusing on flexibility, stability, neuromuscular control, and coordination. The CPT protocol included health education, laser therapy, ultrasound therapy, and exercise. Both interventions were performed for 60 min twice a week for 3 months. The primary outcome was the Knee Injury and Osteoarthritis Outcome Score-4 domain version (KOOS4). Secondary outcomes included pain intensity (VAS), KOOS-pain, activities of daily living (ADL), function in sport and recreation (Sports/Rec), knee-related quality of life, global rating of change (GROC), quality of life (SF-36), Tampa Scale for Kinesiophobia (TSK), and functional performances measured at different intervals. Intention-to-treat analyses were performed. Of the 87 patients, 70 (80.5%) completed the 12-month follow-up. KOOS4 improved more in the APT group (16.13; 95% CI, 10.39–21.88) than in the CPT group (11.23; 95% CI, 5.42–17.04). APT showed additional improvement in KOOS4 compared to CPT (2.94; 95% CI: 0.04 to 5.85, p = 0.047). The VAS difference was −3.41 mm (95% CI: −6.40 to −0.43, p = 0.025), favoring APT. APT also showed more improvements in KOOS-pain, KOOS-ADL, KOOS-Sports/Rec, and TSK (p < 0.05). No differences between groups were observed in GROC and SF-36. APT significantly improved most functional performance variables compared to CPT (p < 0.05). Active Physiotherapy outshines conventional physical therapy by delivering more substantial reductions in pain intensity and marked enhancements in function among patients with knee pain. This distinctive efficacy underscores the invaluable role of APT in the management of chronic knee pain. By actively involving patients in their recovery journey, APT not only fosters superior results but also emphasizes the critical need to integrate these advanced therapeutic strategies into everyday clinical practices.